Factors Determining the Success of Village Fund Allocation Management in Karangharjo Village, Jember: English - Alfinatus Zayyinah; Diana Dwi Astuti; Mustofa (Yayasan Pendidikan Belajar Berdikari, 2025)
Abstract Abstract This research aims to analyze the influence of human resource competencies, accountability, transparency, oversight systems, and community participation on the management of village fund allocation in Karangharjo Village, Silo District, Jember Regency. The background of this research is the disparity in road infrastructure development between hamlets, which indicates that the management of village funds is not optimal. This study uses a quantitative approach with a survey method, collecting data through questionnaires distributed to 80 respondents, consisting of village officials and the community. The sampling technique uses a saturated sampling method, and data analysis is conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression, coefficient of determination (R²), as well as t and F tests with the help of IBM SPSS Statistics 25. The results show that partially, the variables of human resource competence, transparency, and community participation significantly influences the management of village fund allocation. Meanwhile, the variables of accountability and oversight systems do not have a significant effect. The implications of this research indicate that improving the effectiveness of village fund management requires strengthening human resource capacity, information transparency, and active community participation in the planning and implementation of village programs.